Surgical Site Infection, Bacterial Isolates and Their Sensitivity Pattern at Surgical Ward - Bhandari, Sushila Devi (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Surgical site infection is a common occurrence in surgical ward. Knowledge about the commonest pathogen and its sensitivity in a particular setting is crucial in selection of appropriate antibiotics. No study has been performed earlier to identify the pattern of infection and antibiotic sensitivity in surgical department. So, this study aimed to analyze the commonest isolates from surgical site infection and their sensitivity pattern. Methods: A total of 56 cases of surgical site infection who were admitted in surgical ward at Shree Birendra Hospital, were included in this study. Wound swab from the infected surgical site was taken and send for culture and sensitivity. The obtained results were analysed using descriptive tools. Results: Among 56 surgical site infections only in 30 cases a pathogen was isolated. The commonest organism isolated was E.Coli 15(50%) followed by Staph. Aureus. The most sensitive antibiotics was Amikacine for E. Coli, and cefixime for S. Aureus. Conclusions: Ciprofloxacin seems to be the most appropriate first line oral antibiotics as it is sensitive both to E. Coli and S Aureus. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/18-20 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7903